The Influence Of Current Ratio (Cr) And Total Asset Turnover (Tato) On Return On Asset (Roa) At Pt Astra International Tbk For The Period 2009-2024 - Nurmayanti, Fika; Fadli, Achmad Agus Yasin (Jurnal Fokus Manajemen, 2025)
This study aims to analyze the influence of the Current Ratio (CR) and Total Asset Turnover (TATO) on Return on Assets (ROA) at PT Astra International Tbk during the period 2009–2024. The research employs a quantitative approach using multiple linear regression analysis, along with t-tests and F-tests to assess the partial and simultaneous effects of the independent variables on the dependent variable. The findings indicate that, partially, the Current Ratio does not have a significant effect on ROA, with a t-value of 0.745 and a significance level of 0.470 (> 0.05). Conversely, Total Asset Turnover has a significant positive effect on ROA, evidenced by a t-value of 5.198 and a significance level of 0.000 (< 0.05). Simultaneously, both CR and TATO significantly influence ROA, as demonstrated by an F-value of 14.345 and a significance level of 0.001 (< 0.05).